Diagnosis and treatment of emergency surgeries in otorhinolaryngology, head and neck surgery during the covid‐19 outbreak: A single center experience. (1st November 2020) - Sun, Yu; Zhang, Li; Cheng, Qing; Hu, Yujuan; Xiao, Hongjun
Abstract : The 2019 Novel Coronavirus (2019‐nCoV, SARS‐CoV‐2) infection has already been assigned as a Class B infectious disease requiring Class A management strategy according to "the Law on the Prevention and Control of Infectious Diseases of the People's Republic of China" and become a global pandemic. The incidence of emergencies in otorhinolaryngology, head and neck surgery such as foreign bodies in the esophagus and the respiratory tract, epistaxis, laryngeal obstruction with dyspnea, and head and neck trauma are relatively high. Emergency surgeries are required as some of these diseases progress rapidly and probably be life‐threatening. In this article, we drafted the recommendations for diagnosis and treatment of emergency surgeries in otorhinolaryngology, head and neck surgery in the epidemic area of novel coronavirus pneumonia based on "Novel Coronavirus Pneumonia Diagnosis and Treatment Plan (Provisional; 7th Edition Revisions)"and WHO guidelines, combined with the experience of emergency surgeries in the Department of Otorhinolaryngology, Wuhan Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, which is at the center outbreak area of the SARS‐CoV‐2 pneumonia (COVID‐19) in China, to improve the success rate of treatment for otorhinolaryngology, head and neck surgery emergency surgeries and to reduce the SARS‐CoV‐2 infection rate in the perioperative period.